2010
DOI: 10.1038/hr.2010.187
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stretch potentiates angiotensin II-induced proliferation in spontaneously hypertensive rat vascular smooth muscle cells

Abstract: Angiotensin II (AngII) stimulates vascular smooth muscle cell (VSMC) proliferation; however, the effect of AngII on cell proliferation in the presence of mechanical force is not clear. We investigated the mechanism of AngII-induced cell proliferation mediated by mechanical stretch in VSMCs of both normotensive and hypertensive rats. VSMCs obtained from the thoracic aortas of 8-week-old Wistar-Kyoto (WKY) rats and spontaneously hypertensive rats (SHR) were stretched by a Flex culture system. Mechanical stretch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…Mechanical stretch potentiates AngII-induced VSMCs proliferation in spontaneously hypertensive rat through an AT 1 receptor/ EGFR/ERK-dependent pathway. These findings may provide new insights into growth-promoting mechanisms in vasculature in a hypertensive state (Liu et al, 2010). Mechanical stretch triggered an AT 1 receptordependent conformational change in b-arrestin similar to that induced by a b-arrestin-biased ligand (Rakesh et al, 2010).…”
Section: E Signalingmentioning
confidence: 99%
“…Mechanical stretch potentiates AngII-induced VSMCs proliferation in spontaneously hypertensive rat through an AT 1 receptor/ EGFR/ERK-dependent pathway. These findings may provide new insights into growth-promoting mechanisms in vasculature in a hypertensive state (Liu et al, 2010). Mechanical stretch triggered an AT 1 receptordependent conformational change in b-arrestin similar to that induced by a b-arrestin-biased ligand (Rakesh et al, 2010).…”
Section: E Signalingmentioning
confidence: 99%
“…Previous studies showed that Ang II levels in the cell lysate are elevated in human podocytes and HEK293 cells by prorenin stimulation (17, 18). Furthermore, EGF receptor is transactivated via the activation of AT 1 receptor induced by Ang II in VSMCs and HEK293 cells (15, 16, 31). …”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was filtered on Amicon Ultra devises (10 kDa cut-off; Millipore). We measured Ang II concentration by radioimmunoassay using specific antibody for Ang II, monoiodinated 125 I-labeled Ang II, and Ang II standard as previously described (15, 28). In brief, each lyophilized antiserum was diluted sufficiently to yield a specific binding rate after incubation with a 9,000 cpm label for 48 hours at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…That report showed that the synergy is at least partly caused by augmented AT1 receptor expression and is inhibited by ARB. Even in that case, the main action of ARB may be due to its antagonist activity, although inverse agonist activity would have some effect against the overactivity of AT1 receptor due to augmented expression [49,50].…”
Section: Fig 4 Mechanisms Causing Constitutive Gpcr Activationmentioning
confidence: 99%